Increasing Teachers' Commitment to the Organization through Strengthening Self-Efficacy, Organizational Climate and Job Satisfaction - Kurniawan, Andika; Harijanto, Sutci; Wulandari, Farida (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2024)
In an effort to create quality educational institutions that are able to provide knowledge and skills to students and the best educational services, schools must be supported by teachers who are able to support a comfortable learning atmosphere and an effective learning process to develop students' potential. Unfortunately, preliminary research shows that teachers' commitment to the organisation is not fully optimal, so efforts need to be made to improve. This study aims to determine the effect of self-efficacy, organisational climate, and job satisfaction on teachers' commitment to the organisation. Respondents to this study were 126 permanent teachers at private high schools in the Cibinong sub-district, Bogor district, using a questionnaire instrument that was compiled based on indicators of all research variables. This study used a quantitative method with path analysis (path analysis) and SITOREM. The results of the study concluded that there was a very significant positive direct effect: 1) self-efficacy on teachers' commitment to the organisation (?y1=0.351, sig<0.00); 2) organisational climate on teachers' commitment to the organisation (?y2=0.208, sig<0.00); 3) job satisfaction on teachers' commitment to the organisation (?y3=0.419, sig<0.00). 4) there was a direct effect of the self-efficacy variable on job satisfaction, 5) there was a direct effect of the organisational climate variable on job satisfaction, 6) The positive indirect effect of a self-efficacy variable on teacher commitment to the organisation through job satisfaction is equal to (?x13=0.147). 7) The positive indirect effect of organisational climate variables on teacher commitment to the organisation through job satisfaction (?x23=0.087).